Allelopathic potential of Equisetum giganteum L. and Nephrolepis exaltata L. on germination and growth of cucumber and lettuce - Franco, Danilo Miralha [UNESP]; Almeida, Luiz Fernando Rolim de [UNESP]; Poletto, Rodrigo de Sousa (Science Publishing Group, 2014)
Nephrolepis exaltata L. Schott "Bostoniensis" family Davalliaceae and Equisetum giganteum L. family Equisetaceae, Phylum Pteridophyta, exhibit a strong mechanism of dominance in the areas in which they live. Have secondary compounds with allelopathic activity. The objective of this article was evaluate allelopathic potential of two ferns species, using bioassay applying aqueous extracts of dried fronds, in cucumber and lettuce seeds, and observing germination and initial development. To observe the influence on germination was analyze the percentage of germinated seeds and germination speed index (GSI). To observe initial development was analyzed shoot and root growth of the seedlings. The bioassays revealed that no concentration significantly inhibited the germination, but germination speed was delayed gradually in two species tested, as increased the extract concentration. In initial development, all the extracts showed a tendency to inhibit the growth, and an increase in extract concentration decreasing growth of radicle and hypocotyl axis. We conclude that the aqueous extract has inhibitory activity more pronounced in early development than in seed germination, affecting the primary structures of the tested plants, corroborating with the observations of occurrences of the species in natural places where dominate and suppress the growth of other species.
Keywords: Root development; Germination; Crude extract; Equisetum giganteum; Nephrolepis exaltata